Application of Laplace Transform for Solving Improper Integrals containing Bessel’s Function as Integrand, in the form of Hypergeometric Function (Global Journal of Science Frontier Research, 2024)
In this article we use Laplace Transform for solving Improper integrals whose Integrand contains Bessel s function in the form of hypergeometric function The theory of Bessel s function is a rich subject due to its significant role in providing solutions for differential equations associated with many applications Their applications span across disciplines like heat conduction electromagnetism signal processing and more
Keywords: laplace transform; bessel’s function; hypergeometric function; improper integral